Relación entre el acompañamiento familiar y el desempeño escolar en estudiantes de grado 3º de básica primaria de la IED Ofelia Uribe - Mendoza Cortes, Joaquin David (Universidad Antonio Nariño, 2021)
The research sought to establish the relationship between family support and school performance of the third grade primary students of the IED Ofelia Uribe de Acosta. The methodology was framed in a mixed analysis, under a selected sample of a course of 33 students. A sociodemographic survey was applied to those attending that provided elements related to family support and school performance. 6 students with low and high performance were selected according to academic reports, together with their students, interviews were conducted to determine the type of family support, and they were analyzed qualitatively. Concluding that the responsibility for the integral formation of the students is not exclusive to the teachers, the students must assume their role, helping to establish communication channels and thus strengthen the process of school accompaniment.